COLLATERAL GUARANTOR LIABILITY FOR DEBTS OF DEBTORS IN BANKRUPTCY - Hendri Firmansyah; Habib Adjie (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
The insolvency of the debtor has legal consequences on the rights and obligations of the parties involved, including the collateral guarantor. Collateral guarantors have the responsibility to fulfil debt payment obligations if the main debtor is unable to pay off his obligations. This study aims to analyse the obligations of collateral guarantors in cases of debtor bankruptcy based on bankruptcy law in Indonesia. The research method used is normative juridical with a statutory and case approach. The results showed that collateral guarantors still have an obligation to fulfil debt payments even though the main debtor is declared bankrupt, unless there is an agreement that regulates otherwise. In addition, in practice, there are problems related to the execution of collateral and legal protection for guarantors in the bankruptcy system. Therefore, there is a need for legal certainty and a clearer protection mechanism for collateral guarantors in order to create a balance between the interests of creditors and guarantors. This research will discuss how bankruptcy law in Indonesia regulates the obligations of collateral guarantors in the event that the debtor experiences bankruptcy. This research will also analyse the problems that often arise in practice, and provide recommendations to clarify the legal protection mechanism for collateral guarantors.